Pneumonia mikotik pada seekor kucing domestik yang disebabkan oleh Mycoleptodiscus indicus memiliki potensi zoonosis dan dapat menimbulkan ancaman terhadap keamanan nasional. - Puspitayani, Putu Mira; Maarif, Syamsul; Kurniawan, Lilik; Kurniadi, Anwar; Wilopo; Sukariada, I Putu Juli; Ludji, Sherli Melani (ARSHI Veterinary Letters, 2025)
Environmental conditions play a critical role in disease transmission in companion animals, particularly in humid settings that facilitate pathogen proliferation and spread. Mycoleptodiscus indicus is an opportunistic, saprobic, and endophytic fungus that causes systemic infections in various hosts, including humans. This case report describes a fatal M. indicus infection in a kitten. Diagnosis involves clinical examination, cytology, fungal culture, necropsy, and histopathological analysis. Gross pathology revealed swelling and hemorrhage in the heart, spleen, kidneys, and liver, with pulmonary necrosis and hemorrhage. Histopathological examination revealed the presence of fungal spores in the pulmonary tissue. Cytological and culture analyses confirmed the presence of M. indicus. The kitten's death resulted from respiratory invasion by M. indicus spores, which led to systemic dissemination and sepsis.